Quantifying the diffused benefit from water fluoridation in the United States - Griffin SO, Gooch BF, Lockwood SA, Tomar SL (Blackwell Synergy, 2001)
To estimate the total contribution of water fluoridation to caries reduction by including the benefit from the diffusion of fluoride from fluoridated communities to surrounding nonfluoridated communities via the export of bottled beverages and processed foods